(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Mathematics plays an inevitable role in medical science. Numbers are very essential in providing information to doctors, nurses, as well as patients. In ancient India, the place of modern mathematics was occupied by Ganitha shastra. Ganitha shastra is defined as the science and art of computation that has its origin in India. It deals with various branches like mathematics, computing, logic, analytics etc. It is a dominant part of Indian culture and heritage. It has its influence on other Indian systems like Ayurveda. Many examples which authenticate that Ayurveda has not ignored Ganitha Shastra are traceable in classics like Charaka Samhita. Charaka Samhita is an age old Ayurveda compendium which is known for its effective conglomeration of medicine and philosophy. This article is intended for analyzing the influence and utility of Ganitha shastra in Charaka Samhita.